Experimental study on the oxidation behaviors of Wolfcamp light crude oil and its saturate, aromatic and resin fractions using accelerated rate calorimetry tests. (15th September 2020) - Yang, Lingfeng; Sheng, James J.
Highlights: Combined analysis of temperature and pressure trends in the closed ARC tests. Pressure effects on crude oil and its saturate, aromatic and resin (SAR) fractions. Traces of natural antioxidant from the aromatic and the resin fractions of crude oil. Endothermic reactions that cause the negative temperature coefficient (NTC) region of hydrocarbons. Abstract: The air injection process (AIP) has long been applied to enhance crude oil recovery. Oxidation of crude oil is essential for the success of air injection projects. However, the lack of accurate descriptions of the crude oil oxidation has led to incorrect predictions of crude oil oxidation behavior. Compared with the conventional method to characterize crude oil by density and viscosity, saturate, aromatic, resin, and asphaltene (SARA) analysis has proved to be robust for studying crude oil oxidation. Also, accelerated rate calorimetry (ARC) has proved to be suitable for evaluating adiabatic self-heating behavior. This study combined the SARA analysis with ARC tests to determine the details of crude oil oxidation. This paper first reviews the laboratory techniques for studying crude oil oxidation. Then it presents ARC tests on Wolfcamp light crude oil and its saturate, aromatic, and resin fractions. Due to its extremely low concentration in Wolfcamp oil, the asphaltene fraction was not tested during this study. Compared to 50 bar tests, all tested fractions showed enhanced LTO exotherm during 100 bar tests. Also, from the ARC temperature and pressure curves, we identified two endothermic processes that might cause a negative temperature coefficient region. One endothermic process showed decreasing trend in pressure while the other process showed increase in pressure. Finally, evidence of natural antioxidants was found after testing mixtures of saturates with other fractions. Those chain-breaking antioxidants can decelerate the fast-oxidation behavior of saturates. This paper provides details of the crude oil oxidation process derived from experiments.